USE OF CLOSED CIRCUIT TELEVISION (CCTV) FOR ENSURING QUALITY LEARNING AND INTERNAL POLICING IN EARLY YEARS CENTERS - Aimiuwu, Moses A.; Bosah, Ifeoma P. (Journal of Early Childhood and Primary Education, 2020)
This study examined the use of Closed Circuit Television (CCTV) surveillance cameras for ensuring quality learning and internal policing in early years centers in Delta State.  The study was piloted by three research questions which were answered and two hypotheses which were tested at a level of significance of 0.05. The study was a descriptive survey had a population of six hundred and eighty-eight (688) Private Early Childhood Care Centers spread across the 25 Local Government Areas of Delta State. A total of 79 Caregivers and 60 Attendants were selected and used for the study through a purposive random sampling method. The structured questionnaire for data collection titled; â€˜Impact of Closed Circuit Television Surveillance Camera in Monitoring and Ensuring Quality Care-givingâ€™(ICCTSCMEQCG) was validated prior to its use by two Chief Lecturers in Measurement and Evaluation, College of Education, Agbor and another Chief Lecturer from the Department of Early Childhood and Primary Education, Nnamdi Azikiwe University, Awka.  The study questionnaire had its reliability determined at a coefficient of 0.84, using Cronbach Alpha reliability test and was personally administered to the sample with 95% retrieval rate.  The mean and standard deviation statistical techniques were used to answer the two research questions, while t-test was used to test the stated null hypotheses. Study results revealed that there are great impact if Closed Circuit Television (CCTV) surveillance camera is used for ensuring quality learning and internal policing in early years centers, amongst others, Care giving will be done at the best when caregivers and attendants are aware of being watched by the installed closed circuit television cameras. Also pupils learning activities are easily monitored on playback from the recorded tape of the camera system.  Flowing from the findings, it was recommended that public early childhood care centres should key-in into the technology drive of the use of closed circuit television surveillance cameras for ensuring quality learning and internal policing early yearsâ€™ centres.
Keywords: Closed-Circuit Television (CCTV); I.P Camera; Monitoring; Evaluation; Curriculum; Surveillance; Quality; Care-giving; Feedback; Scaffolding; Curriculum Policing